Theoretical foundations and methodological bases for curriculum mainstreaming in higher education (Revista Electrónica Calidad en la Educación Superior, 2019)
The purpose of this article is to gather and analyze the most relevant aspects of the foundations and methodological bases for curriculum mainstreaming, which allows us to show the considerations taken for establishing educational proposals and implement them from this perspective, based on the vision of education and curriculum that the intertwining courses requires. The aim of the intertwining courses is to establish a connecting point between social realities and disciplinary knowledge; this allows us to overcome the much criticized -but until now- strong curriculum fragmentation, having as the ultimate goal -of which social responsibility is an essential competence- to be used in the educational process of each professional, and to add it to each challenge and duty of the universities. Therefore, this article is aimed at those people who face the challenge of teaching in such areas as: curricular design, evaluation of learning, development of materials, training, and teacher mediation. This approach of curriculum mainstreaming demonstrates the need to think about formative proposals with an evident orientation towards the sociocritical, humanistic, and interdisciplinary actions with a global perspective. What allows us to conclude that the mainstreaming course subjects is a way of organizing the whole curriculum and not just some aspects in it, this must transcend the prescribed, pivotal moment for its implementation, where not only is required to understand the very nature of each subject, but also the methodological treatment of mainstreaming.
Keywords: mainstreaming; higher education; curriculum